Photographic Photometry of NGC 6866 - B. Hidajat; W. Sutantyo (Journal of Mathematical and Fundamental Sciences, 1972)
Abstract. Magnitudes and colors in the UBV photometric system have been determined for 575 stars in and around NGC 6866. The color-color relation of the cluster stars provides an estimate of interstellar reddening of 0.16 mag. The distance of cluster is found to be 1336 pc. The age, as determined from the evolutionary deviation curve, is approximately 2.5 x 108 years.  Ringkasan. Magnitudo dan warna dalam sistim UBV-photometri untuk 575 buah bintang disekitar NGC 6866 telah diukur setjara photographi-photometri. Excess warna, jang diturunkan dari diagram warna-warna, telah ditentukan sebesar 0.16 magnitudo. Djarak gugus bintang tersebut diperkirakan 1336 pc. Dari kurva evolusi diketahui bahwa umur gugus tersebut 2.5 x 108 tahun.